Karya Prof. Phalgunadi “Sekilas Sejarah Evolusi Agama Hindu”: Menelisik dan Memahaminya dalam Bingkai Filsafat Sejarah Hindu - Putu Eka Sura Adnyana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Lately there have been many debates and open discussions on social media related to the problem of clashing beliefs between Balinese Hinduism and Hare Khrisna (HK).One literacy that deserves to be an important reference is the work carried out by Prof. Dr. Litt. Dr. I Gusti Putu Phalgunadi, M.A., entitled A Brief History of the Evolution of Hinduism. This article analyzes and traces Prof. Phalgunadi's thoughts in describing the evolution of Hinduism from 1) the Sindhu River Valley Civilization (3,000 SM-2000 SM), 2) the Vedic Period (2000 SM-1000 SM), 3) the Brahmin Age (1,000 SM-300 M), 4) The Purana Period: The Golden Age of Hindu Religion and Culture (300 M- 700 M), 5) The Reformation Age of Hinduism (Sangkaracharya Period 700 M-1,200 M), 6) The Age of the Bhakti Movement (1,200 M-1,800 M) and 7) the Movement Modern Hinduism (1,800 M-1947 M). The current debate between Hindu Bali and Hare Khrisna clearly has a different frame as the evolution in Hinduism itself, moreover this debate is taking place in the territory of Republic Indonesia so that it must pay attention to the constitution which applies